Behavior of alfalfa under different soil acidity levels - Kornelius, Euclides; Ritchey, Kenneth Dale (Pesquisa Agropecuaria Brasileira, 1992)
Alfalfa (Medicago sativa L. cv. Crioula) was evaluated in a Dark-Red Latosol which received in 1972 three levels of calcitic lime (7.5 - 15.0 and 22.5 t/ha) and three levels of Zn (zero, 3 and 9 kg/ha). A factorial design in randomized blocks was used with four replications. Zn did not affect alfalfa yield. Yields increased with increasing lime levels. Lime affected pH, Al, Ca and Mg levels in the soil. This effect was dipper in the profile with higher levels of lime. Levels of N, P, K, Ca and Mg in dry matter seams to be adequate to good alfalfa growth.